Change in birth registration from place of birth in Kyiv through surrogacy to the place of residence of the parents in Barcelona: regarding the Judgment of the Suprem Court 17th September 2024 - Castellanos Ruiz, Mª José (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In this case, the intended parents requested the transfer of their child’s birth registration to the Barcelona Civil Registry and that the child’s place of birth be registered not in the place where he was born abroad, Kyiv, but in the parents’ residence, Barcelona. Although the lower courts make special mention of the child’s birth through surrogacy, this does not, in principle, have any real significance for the case at hand, as the Supreme Court emphasized in its judgment of 17th September 2024. However, it is relevant in the sense that this judgment is giving certain effects to surrogacy contracts, those that are less harmful to the basic structure and cohesion of Spanish society, speaking in terms of attenuated public order. However, the most significant effects regarding surrogacy contracts concluded in Ukraine had already occurred previously: the recognition of parentage in Spain in favor of the commissioning parents, which is discussed extensively in the paper. In this sense, it was a missed opportunity for the Supreme Court to assess the legality of surrogacy contracts, specifically those concluded in Ukraine, as it has done in previous judgements.